Effects of 12-step mutual support and professional outpatient services on short-term substance use outcomes among adults who received inpatient treatment. (November 2019) - Costello, Mary Jean; Li, Yao; Remers, Shannon; MacKillop, James; Sousa, Sarah; Ropp, Courtney; Roth, Don; Weiss, Mark; Rush, Brian
Abstract: Background: Continuing care is increasingly prioritized in the treatment of substance use disorders (SUDs). Ongoing engagement in continuing care, including mutual support (e.g., 12-step groups) and/or professional outpatient services, may enhance treatment outcomes and facilitate recovery. Objective: This study investigates how engagement in 12-step mutual support and professional outpatient services is associated with short-term substance use outcomes in a sample of patients who completed inpatient SUDs treatment. Methods: As part of the Recovery Journey Project – a longitudinal cohort study – participants completed questionnaires upon admission to an inpatient SUDs treatment program, and at 1- and/or 3-months post-discharge ( n  = 379). Baseline data were collected by self-administered, electronic questionnaires. Follow up data were collected by phone or email. Analyses involved multivariate Generalized Estimating Equations separately modelling self-reported abstinence and percent days abstinent (PDA) over the three time periods. Results: Overall, rates of self-reported abstinence and PDA increased significantly from baseline to 1- and 3-months follow up. Engagement in 12-step activities (i.e., attended 30 meetings in 30 days, had a home group, had a sponsor, did service work) and professional outpatient substance use support were each significantly associated with abstinence and PDA. Participants who reported a higher degree of 12-step involvement (defined as engagement in more 12-step activities) were also more likely to report being abstinence and greater PDA. Conclusions: Engagement in continuing care, including 12-step activities and professional outpatient substance use support, was highly associated with substance use. Clinical teams should encourage participation in such activities to optimize treatment outcomes. Highlights: Self-reported abstinence improved over time following inpatient treatment. 12-step group activities and outpatient addiction support were associated with abstinence. Higher degree of involvement in 12-step groups was associated with better outcomes. Engagement in continuing care enhanced inpatient treatment outcomes.